2017
DOI: 10.1111/evo.13321
|View full text |Cite
|
Sign up to set email alerts
|

Male and female contributions to behavioral isolation in darters as a function of genetic distance and color distance

Abstract: Determining which reproductive isolating barriers arise first between geographically isolated lineages is critical to understanding allopatric speciation. We examined behavioral isolation among four recently diverged allopatric species in the orangethroat darter clade (Etheostoma: Ceasia). We also examined behavioral isolation between each Ceasia species and the sympatric rainbow darter Etheostoma caeruleum. We asked (1) is behavioral isolation present between allopatric Ceasia species, and how does this compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
125
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(142 citation statements)
references
References 102 publications
12
125
5
Order By: Relevance
“…This pattern is consistent with recent work on darter fish, which showed that only males diverged in their mating preferences (Moran et al. ; Mendelson et al. ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern is consistent with recent work on darter fish, which showed that only males diverged in their mating preferences (Moran et al. ; Mendelson et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a recent comparative study examined male and female mating preferences between multiple species of darter fish (Martin and Mendelson ; Moran et al. ; Mendelson et al. ).…”
mentioning
confidence: 99%
“…Regardless of the mode of selection acting on male mate choice, our results highlight the potentially significant and often overlooked role of male choice in reproductive isolation and speciation, adding to recent findings in other systems (Moran et al. ). We suggest that further study of the mechanisms by which male mate discrimination evolves would provide valuable insight into the selection pressures driving the formation of reproductively isolating barriers.…”
Section: Discussionsupporting
confidence: 75%
“…Moran et al. () also concluded that male preference for conspecifics is stronger than females’ among recently elevated species in the E. spectabile group. Finally, our finding that male preference for conspecific females is greater than female preference in artificial stream assays, where individuals have full physical access, further supports the conclusion that male preference for conspecific mates is stronger at early stages of divergence than females’.…”
Section: Discussionmentioning
confidence: 96%
“…), and several studies demonstrate that male darters have strong preferences for (i.e., bias their aggression toward) conspecific color patterns (Williams and Mendelson , Martin and Mendelson , Moran et al. ). If a novel ornament is more intimidating than the average signal, males with that ornament will win access to females, and selection will favor its spread.…”
Section: Discussionmentioning
confidence: 99%